Avaliação da ação do receptor de estrógeno beta e a função de NOX2 na osteoclastogênese e na atividade de osteoclastos. - Uehara, Isadora Akemi (2020)
Chapter 1: Postmenopausal women are more susceptible to the development of osteoporosis, a disease characterized by greater osteoclast-mediated bone resorption. Estrogen, one of the main hormones affected during menopause, is known to be important for bone protection. Estrogen acts through two classic receptors, the estrogen receptor α and β. There is a lack about the relationship between ERβ and osteoclast in the literature. Therefore, the objective of this work was to evaluate the effect of ERβ on osteoclastogenesis using diarylpropionitrile (DPN), a selective agonist for the receptor. The expression of the receptor in cells stimulated only with RANKL (receptor activator of nuclear factor kappa-Β ligand) was evaluated by real-time PCR and a higher gene expression was found in 72h. DPN did not change the number, area of osteoclasts, actin polymerization and not even their resorption capacity. Incubation with 17β-estradiol (E2), on the other hand, was able to reduce the area of osteoclasts, which also demonstrated that their resorptive capacity was reduced, however no effect was seen in actin ring polymerization. Thus, it may be that ERβ has no significant action on osteoclasts and the effects observed in use of estrogen are mediated by ERα. Chapter 2: Osteoclastogenesis is the differentiating process of hematopoietic cell lineage into mature osteoclasts (cells responsible for bone resorption). The imbalance in the action of osteoclasts in favor of greater bone resorption generates diseases such as osteoporosis. Elucidating the signaling pathways that lead to osteoclastogenesis is important to understand mechanisms that can become therapeutic targets for treating diseases that affect bone tissue. To occur osteoclastogenesis, intracellular signals derived from stimulus by cytokines are necessary, the main ones being the macrophage stimulating factor (M-CSF) and RANKL. Reactive oxygen species (ROS) have been described as molecules that act as secondary messengers in several signaling pathways and have been described as inducing differentiation and activity of osteoclasts. NADPH oxidase (NOX) are the main producers of ROS and have seven isoforms. In this work, NOX2 was evaluated in osteoclastogenesis using the knockout mouse for this isoform (NOX2-/-). The results showed that osteoclast differentiation was not affected by the absence of NOX2, which suggests that this isoform is not essential for osteoclastogenesis. Although it did not change the differentiation, an increase in the intracellular calcium influx and consequently an increase in the cathepsin K gene expression evaluated by real-time PCR was seen. In addition, there was an increase in bone resorption by NOX2-/- mouse cells, probably due to the increase in cathepsin K.